Current trends in Industry 4.0 and Supply Chain from 2020 to 2023: A Systematic Literature Review - Rojas Sánchez, David Isaí; Callupe Macuri, Juan Manuel; Rodríguez Cucho, Kenneth Rubén; Marcilla Pascua, Leonela Eymi; Romero Cisneros, Mónica Milagros; Santa Cruz Salazar, Jorge Alfonso; Moscoso Cuaresma, Julio Ricardo (LACCEI, 2024)
Over time, markets have evolved and become increasingly complex, due to this, supply chain management requires greater flexibility and adaptability. Therefore, the purpose of this study is to analyze the current trends and elements that make up industry 4.0 and the Supply Chain. The chosen methodology was a systematic review of the literature and 40 articles that were published before March 2023 were analyzed. Based on the analysis of the literature, this study explores the landscape of Supply Chain and I4.0 research, discovering its strong connection through 3 fundamental factors: sustainability, the agents involved, and finally, digitalization. The originality and value of this study is based on providing a new perspective of the articles published under the theme of Industry 4.0 and Supply Chain. Likewise, it proposes a framework to evaluate that can be used in future research.